Helicobacter pylori Induces Apoptosis of Human Monocytes but Not Monocyte-Derived Dendritic Cells: Role of the cag Pathogenicity Island - Galgani, Mario (American Society for Microbiology, 2004)
Monocytes are circulating precursors of the dendritic cell subset, professional antigen-presenting cells with a unique ability to initiate the innate and adaptive immune response. In this study, we have investigated the effects of wild-type Helicobacter pylori strains and their isogenic mutants with mutations in known bacterial virulence factors on monocytes and monocyte-derived dendritic cells. We show that H. pylori strains induce apoptosis of human monocytes by a mechanism that is dependent on the expression of a functional cag pathogenicity island. This effect requires an intact injection organelle for direct contact between monocytes and the bacteria but also requires a still-unidentified effector that is different from VacA or CagA. The exposure of in vitro-generated monocyte-derived dendritic cells to H. pylori stimulates the release of inflammatory cytokines by a similar mechanism. Of note is that dendritic cells are resistant to H. pylori-induced apoptosis. These phenomena may play a critical role in the evasion of the immune response by H. pylori, contributing to the persistence of the infection.